Microstructural consequences of isothermal crystallization in homo- and co-polyesters based on 2, 5- and 2, 4-furandicarboxylic acid. (17th April 2023) - Bourdet, Aurélie; Fosse, Clément; Garda, Marie-Rose; Thiyagarajan, Shanmugam; Delbreilh, Laurent; Esposito, Antonella; Dargent, Eric
Abstract: Different position isomers of furandicarboxylic acid (FDCA) can be obtained from the biomass by a Henkel disproportionation reaction. 2, 5- and 2, 4-FDCA are obtained in amounts that are large enough to be used for the synthesis of polyethylene furanoate (PEF). The homopolyesters obtained with ethylene glycol (EG) and either 2, 5- or 2, 4-FDCA have a completely different crystallization behavior, for 2, 5-PEF can crystallize whereas 2, 4-PEF cannot, even after very long annealing times. The synthesis of random copolyesters with EG and different ratios of 2, 5/2, 4-FDCA may therefore allow to tune PEF crystallization ability. The partial replacement of 2, 5-FDCA by its position isomer could help disrupting crystallinity analogously to what happens when EG is partially replaced by cyclohexane dimethanol (CHDM) in glycol-modified polyethylene terephthalate (PETg). This work investigates the thermal behavior of the homopolyester 2, 5-PEF and the microstructural consequences of copolymerization (replacement of small amounts of 2, 5-FDCA with 2, 4-FDCA). Crystallization is performed in isothermal conditions after cooling down from the molten state, and investigated with both conventional DSC and Fast Scanning Calorimetry (FSC). When the amount of 2, 4-FDCA-based repeating units is low (10 and 15 mol %), crystallization still occurs but with an increased induction time. Neither the crystalline nor the rigid amorphous fractions are significantly affected by copolymerization. Due to multiple and complex microstructural reorganizations observed at relatively slow heating rates, conventional DSC is inaccurate and does not provide a reliable microstructural depiction of these polyesters. The use of FSC is recommended, for it allows to obtain a better characterization of the quality and thermal stability of the formed crystals. Graphical abstract: Image 1 Highlights: The presence of 2, 4-FDCA in 2, 5-FDCA-based copolyesters tunes their crystallization. Up to 10–15 mol% 2, 4-FDCA, crystallization occurs with an increased induction time. Neither the crystalline nor the rigid amorphous fractions are significantly affected. FSC is recommended to characterize the quality and thermal stability of the crystals. Only small values of XRAF were observed, with little (if any) correlation with XC .